2018
DOI: 10.1071/ch18271
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the Challenges of Hydrogenation in Silicon Solar Cells

Abstract: The challenges of passivating defects in silicon solar cells using hydrogen atoms are discussed. Atomic hydrogen is naturally incorporated into conventional silicon solar cells through the deposition of hydrogen-containing dielectric layers and the metallisation firing process. The firing process can readily passivate certain structural defects such as grain boundaries. However, the standard hydrogenation processes are ineffective at passivating numerous defects in silicon solar cells. This difficulty can be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 87 publications
(120 reference statements)
0
8
0
Order By: Relevance
“…[161][162][163] Furthermore, thermal processes are also known to precipitate iron. 158,164,165 Another defect of key importance for silicon solar cells with contradictions in the literature is the boron-oxygen (B-O) complex, 60,[166][167][168] responsible for carrier-induced degradation in ptype Czochralski (Cz) silicon. 169,170 The challenge of hydrogen detection has no doubt played a role in this controversy, with estimated defect concentrations in the range of 10 11 to 10 13 /cm Subsequent work has provided further evidence for the role of hydrogen, by identifying the influence of the hydrogen concentration and thickness of dielectric layers in the passivation reaction.…”
Section: E D = E C -0:16 Ev ð1þmentioning
confidence: 99%
See 2 more Smart Citations
“…[161][162][163] Furthermore, thermal processes are also known to precipitate iron. 158,164,165 Another defect of key importance for silicon solar cells with contradictions in the literature is the boron-oxygen (B-O) complex, 60,[166][167][168] responsible for carrier-induced degradation in ptype Czochralski (Cz) silicon. 169,170 The challenge of hydrogen detection has no doubt played a role in this controversy, with estimated defect concentrations in the range of 10 11 to 10 13 /cm Subsequent work has provided further evidence for the role of hydrogen, by identifying the influence of the hydrogen concentration and thickness of dielectric layers in the passivation reaction.…”
Section: E D = E C -0:16 Ev ð1þmentioning
confidence: 99%
“…212 The most recent study also identified the differences in passivation with illuminated versus dark hydrogenation processes for laser-induced defects, highlighting the impact of advanced hydrogenation processes for the heavily doped silicon regions. 60 Additional low-temperature hydrogenation processes have also proven extremely beneficial for dislocation clusters in cast-mono material, with efficiency enhancements of up to 2% absolute. 204,217,218 However, the specific benefit of illumination in these processes remains unclear.…”
Section: Advanced Hydrogenation Of Silicon Solar Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is also the case for PERC solar cells, where high-temperature firing allows hydrogen to move from the dielectric layers to passivate both bulk and surface defects. 21,22 In p-type PERC solar cells, it is typical to also include a secondary dedicated hydrogenation step on the cell after metallisation. This approach is often referred to as an 'advanced hydrogenation process' and involves carrier injection, either via illumination or direct current injection.…”
mentioning
confidence: 99%
“…Additional low-temperature hydrogenation processes implemented after the conventional fast-firing hydrogenation process are shown to improve the passivation of difficult structural defects. [3] Liam Burt (University of Tasmania) was awarded the Masson Memorial Scholarship, and in a Highlight co-written with his supervisor, Curtis Ho, on high oxidation states of organopalladium(IV) species, it is recalled that the synthetically versatile palladium-catalysed couplings usually employ palladium (0)/palladium(II) catalysis, and there is much less knowledge of palladium(II)/palladium(IV) pairs. The Highlight focuses on seminal discoveries in organopalladium(IV) chemistry and their applications in palladium catalysis, particularly C-H activation.…”
mentioning
confidence: 99%